How do companies deal with tax consequences of investment proposals? - Hong, Jinning (2006)
This dissertation investigates how the tax management issues are handled in organisations and how circularity affects the design of corporate structure in the UK pharmaceutical sector. Interviews are used as a primary research methodology, and this study offers in-depth explanations of current practice. Based on the interviews with three of the largest UK pharmaceutical companies, a firm understanding about tax management and the structural design within companies is developed. Analysis illustrates the strengths and weaknesses of each company's approach to issues of taxation. The research findings and analysis presented will stimulate those involved in major capital investment decision-making to consider their present practices in light of knowledge of policies and techniques of tax management adopted by other companies.